"Socialization for Scarcity" in Emergency Management: Rethinking Assumptions of Resource Scarcity in Humanitarian Crises. Issue 1 (24th March 2023) - Fanning, Zoe
Background: Physician-anthropologist Paul Farmer theorizes a process of "socialization for scarcity" (SfS), which assumes permanent and unchangeable resource scarcity for the world's poor. International health and poverty decisions that are based off of this premise are therefore used to justify inadequate care for vulnerable populations. Objectives: The theory of SfS has predominantly been applied to the context of global health and development. This paper aims to apply SfS to the field of emergency management, asking, "How does SfS function in the context of humanitarian crises, and what implications does this have for emergency management?" Methods: This paper reviewed Farmer's own descriptions of SfS as well as articles by colleagues and other scholars who elaborated on his theory, analyzing their contributions to issues relevant in emergency management. Findings: This review finds that SfS is both applicable to and amplified within emergency management because of the uncertain, competitive, and urgent nature of humanitarian crises. The paper then describes potential approaches to combating SfS in emergency contexts. Conclusions: SfS is the result of deficient effort toward discovering approaches to managing emergencies that do not presume scarcity. The assumption of permanent resource scarcity, especially in low- and middle-income countries (LMICs), is a matter of inequity and injustice and stands opposed to imperative systemic change. Emergency managers must work to eradicate dangerous presumptions that leave already suffering individuals even further from the dignified, appropriate and adequate care they require and deserve.